How to deal with resale price maintenance: What can we learn from empirical results? - Jürgen-Peter Kretschmer (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
The US Supreme Court's overruling of the pre-existing per se illegality of resale price maintenance and the recommendation of a rule of reason approach in the Leegin decision (2007), raise the question whether other jurisdictions should follow this approach and what future assessments of resale price maintenance cases should look like. Policy decisions have to rely on the importance of various theories concerning welfare effects of resale price maintenance practises, which must be supported by empirical studies. Unfortunately, not much attention has been paid to this topic by researchers. Nevertheless, the few existing empirical studies allow for the analysis and discussion of existing assessment proposals. Furthermore, the paper derives a new recommended assessment procedure for resale price maintenance from a special point of view by combining empirical results with the decision-theoretic approach of optimal sequential investigation rules.
Keywords: K21; K40; L42; D81; 330; antitrust law; law enforcement; resale price maintenance; decision-making; Preisbindung; Kartellrecht; Rechtsdurchsetzung; Mehrstufige Entscheidung; USA